IMPORTANȚA DREPTURILOR ȘI LIBERTĂȚILOR ÎN ECONOMIA PIEȚEI LIBERE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The importance of rights and freedoms in the free market economyThis paper is dedicated to the issue of rights and freedoms, the different degrees of freedom, as well as the consequences that differences or variations of freedom have on development, especially on the economic one. The theme of rights and freedoms, in particular, economic freedom, which is expressed primarily through the form of ownership and the scope of the free market, occupies a special place. Both factors depend on how the state works, especially the degree to which its degree of involvement in the economy works. Other and other dimensions of development, professional training, stability of the national currency, the level of taxes, the nature of financial institutions are also important. It is also very important the role and interdependencies that are established between freedom, inequality and development. It is important that freedom is understood in relation to man as an individual, not to social groups treated separately by the individuals who make them up. It is, therefore, an individualistic vision of rights and freedom, correlated with the idea of value attributed to the human individual as uniqueness. It is from this aspect that we should start, respectively, considering that it would be necessary to characterize our struggle for national freedom, respectively for collective rights and freedoms. At the heart of this struggle, however, should be a kind of individualism: its goal should be that at least some of the individuals of our ociety, to obtain greater freedom and not to be obstructed by foreign interests.